Matching-Adjusted Indirect Comparison of the Efficacy and Safety of Erdafitinib vs Enfortumab Vedotin in Patients with Locally Advanced Metastatic Urothelial Carcinoma - Suzy Van Sanden; Ayman Youssef; Simona Baculea; Keith Stubbs; Spyros Triantos; Zijiao Yuan; Caitlin Daly (Journal of Health Economics and Outcomes Research)
**Background:** For patients with locally advanced or metastatic urothelial carcinoma (la/mUC), prognosis is poor and effective treatment options are limited. Erdafitinib is an oral fibroblast growth factor receptor (FGFR) kinase inhibitor approved by the FDA for the treatment of adults with la/mUC harboring FGFR alterations whose disease progressed following at least 1 prior line of therapy, including a PD-1 or PD-L(1) inhibitor, based on the phase 3, randomized THOR trial (NCT03390504, Cohort 1).